Edoxaban in the Evolving Scenario of Non Vitamin K Antagonist Oral Anticoagulants Imputed Placebo Analysis and Multiple Treatment Comparisons - Verdecchia, Paolo (Public Library of Science, 2014)
BACKGROUND: Edoxaban recently proved non-inferior to warfarin for prevention of thromboembolism in patients with non-valvular atrial fibrillation (AF). We conducted an imputed-placebo analysis with estimates of the proportion of warfarin effect preserved by each non vitamin K antagonist oral anticoagulant (NOAC) and indirect comparisons between edoxaban and different NOACs. METHODS AND FINDINGS: We performed a literature search (up to January 2014), clinical trials registers, conference proceedings, and websites of regulatory agencies. We selected non-inferiority randomised controlled phase III trials of dabigatran, rivaroxaban, apixaban and edoxaban compared with adjusted-dose warfarin in non-valvular AF. Compared to imputed placebo, all NOACs reduced the risk of stroke (ORs between 0.24 and 0.42, all p<0.001) and all-cause mortality (ORs between 0.55 and 0.59, all p<0.05). Edoxaban 30 mg and 60 mg preserved 87% and 112%, respectively, of the protective effect of warfarin on stroke, and 133% and 121%, respectively, of the protective effect of warfarin on all-cause mortality. The risk of primary outcome (stroke/systemic embolism), all strokes and ischemic strokes was significantly higher with edoxaban 30 mg than dabigatran 150 mg and apixaban. There were no significant differences between edoxaban 60 mg and other NOACs for all efficacy outcomes except stroke, which was higher with edoxaban 60 mg than dabigatran 150 mg. The risk of major bleedings was lower with edoxaban 30 mg than any other NOAC, odds ratios (ORs) ranging between 0.45 and 0.67 (all p<0.001). CONCLUSIONS: This study suggests that all NOACs preserve a substantial or even larger proportion of the protective warfarin effect on stroke and all-cause mortality. Edoxaban 30 mg is associated with a definitely lower risk of major bleedings than other NOACs. This is counterbalanced by a lower efficacy in the prevention of thromboembolism, although with a final benefit on all-cause mortality.